(untitled) (Medical Forum Monthly, 2023)
Background: Gingival recession is defined as the displacement of the soft tissue margin apical to the cementoenamel junction which leads to compromised esthetics, root sensitivity and even periodontal support for successful orthodontic treatment. This case report aims to describe the surgical management of a Miller’s class II gingival recession prior to orthodontic treatment. Place and Duration of Study: This study was conducted at the Department of Periodontics, Malabar Dental College, Kerala, India from 05.01.2022 to 03.01.2023. Case Presentation: A 29-year-old male presented to the Department of Periodontics, Malabar Dental College, Kannur with a chief complaint of spacing of anterior teeth and unsatisfactory esthetics of anterior teeth. A history of sensitivity in the anterior teeth region was noted. Miller’s class II gingival recession was present along 31,41 and 42. The recession defect altogether measured 3-5mm apico-coronary and 14 mm mesio-distally. A free autogenous gingival grafting for the recession was done to achieve root coverage and increase the attached gingiva after scaling and root planning. Conclusion: Free gingival grafting for root coverages in Miller class II recession before orthodontic treatment offers better periodontal support and esthetics.